Protective Action of Carica papaya on β-Cells in Streptozotocin-Induced Diabetic Rats - Miranda-Osorio, Pedro H. (Int J Environ Res Public Health, 2016)
The aim of the present study was to investigate the effect of C. papaya L. leaf extract (CPLE) on pancreatic islets in streptozotocin (STZ)-induced diabetic rats, as well as on cultured normal pancreatic cells with STZ in the medium. CPLE (3–125 mg/Kg) was administered orally for 20 days, while a group of diabetic rats received 5 IU/Kg/day of insulin. At the end of the treatment the rats were sacrificed. Blood was obtained to assess glucose and insulin levels. The pancreas was dissected to evaluate β cells by immunohistochemistry. In addition, normal pancreatic cells were cultured in a medium that included CPLE (3–12 mg). One half of the cultured cells received simultaneously CPLE and STZ (6 mg), while the other half received CPLE and five days later the STZ. After three days of incubation, insulin was assayed in the incubation medium. The CPLE administered to diabetic rats improved the fasting glycemia and preserved the number and structure of pancreatic islets. However, when CPLE was added to pancreatic cells in culture along with STZ, the insulin concentration was higher in comparison with the cells that only received STZ. In conclusion, the CPLE preserves the integrity of pancreatic islets, improves the basal insulin secretion and protects cultured cells from the adverse effects of STZ.